A markup index in determining possible market power abuse in the electricity market - Arceo, Aldrick P.; Pedrasa, Michael Angelo A. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Considered as one of the defects than an energy-only market is the presence of market power. It progresses as an electricity producer exercises capacity holding that results in price-quantity distortion. As an effect, the producers will be able to receive profit as determined by the price-quantity outcomes that will come from the wealth transferred from the consumers. A monitoring index, called the markup index, is created using a duopoly market model analysis that measures the degree of breach done after a producer performed capacity withholding. Further, a monitoring framework that incorporates the markup index is created to identify market power abuse. The framework was successful in identifying if capacity withholding could result in market power abuse or breach of the market rules. Moreover, the framework identified that market power abuse could be successfully done by any producer at any given season or trading interval given at the supply curve that serves the demand is steep, the capacity withheld by a producer is large enough to cause price distortion and the marginal cost of the withheld capacity is a price setting plant. A limitation, however, was noted when additional plants was dispatched from a producer that withheld capacity. Continuous research efforts related to identification of conditions that corresponds to market power abuse are imperative in any energy market where effective competition is undermined.
Thesis (M.S. Energy Engineering)--University of the Philippines Diliman
Keywords: Electric utilities -- Philippines; Electric power -- Marketing; Marketing -- Mathematical models